Comprehensive assessment of dissolved organic matter processing in the Amazon River and its major tributaries revealed by positive and negative electrospray mass spectrometry and NMR spectroscopy - Li, Siyu; Harir, Mourad; Schmitt-Kopplin, Philippe; Gonsior, Michael; Enrich-Prast, Alex; Bastviken, David; Valle, Juliana; Machado-Silva, Fausto; Hertkorn, Norbert (The Science of the total environment, 2023)
Rivers are natural biogeochemical systems shaping the fates of dissolved organic matter (DOM) from leaving soils to reaching the oceans. This study focuses on Amazon basin DOM processing employing negative and positive electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI[±] FT-ICR MS) and nuclear magnetic resonance spectroscopy (NMR) to reveal effects of major processes on the compositional space and structural characteristics of black, white and clear water systems. These include non-conservative mixing at the confluences of (1) Solimões and the Negro River, (2) the Amazon River and the Madeira River, and (3) in-stream processing of Amazon River DOM between the Madeira River and the Tapajós River. The Negro River (black water) supplies more highly oxygenated and high molecular weight compounds, whereas the Solimões and Madeira Rivers (white water) contribute more CHNO and CHOS molecules to the Amazon River main stem. Aliphatic CHO and abundant CHNO compounds prevail in Tapajos River DOM (clear water), likely originating from primary production. Sorption onto particles and heterotrophic microbial degradation are probably the principal mechanisms for the observed changes in DOM composition in the Amazon River and its tributaries. [Display omitted] •Unveiling DOM molecular and structural characteristics in the Amazon basin•ESI[±] FT-ICR MS and NMR provided comprehensive coverage of DOM processing.•Nitrogen containing molecules are critical partners in the cycling of DOM.•DOM in the Amazon River mixing zones showed non-conservative behavior.•Physicochemical and microbial processes determine DOM changes in the Amazon basin.